PENGARUH SUHU YANG BERBEDA TERHADAP PERTUMBUHAN DAN TINGKAT KELANGSUNGAN HIDUP SPAT KERANG MUTIARA (Pinctada maxima) - Mayunita, Alfina Laila; Mukhlis, Alis; Mulyani, Laily Fitriani (Journal of Fish Nutrition, 2024)
This study aimed to evaluate the effects of different temperatures on growth, feed filtration rate, and survival rate of pearl oyster spat (Pinctada maxima). The research was conducted using a Completely Randomized Design with three temperature treatments (control/room temperature 29-31°C, 32°C, and 34°C) and four replications. Twenty-five-day-old spats were reared for 21 days in containers containing 10L of seawater with a density of 75 spats per container. Results showed that temperature significantly affected (p<0.05) spat growth and filtration rate. The highest growth was found at 34°C treatment with absolute growth of 5.11±0.05 mm, relative growth of 211.2±2.25%, and specific growth rate of 5.55±0.04%/day. The highest filtration rate was also recorded at 34°C (140.4±2.1 ml/hour/spat). However, the highest survival rate was found at 32°C (83.3±2.6%). These results indicate that temperatures of 32-34°C can be recommended for pearl oyster spat cultivation, considering the balance between optimal growth and survival rate.